Wastewater treatment and reuse in urban agriculture: exploring the food, energy, water, and health nexus in Hyderabad, India - Miller-Robbie, Leslie; Ramaswami, A.; Amerasinghe, Priyanie H. (IOP Publishing, 2017)
Nutrients and water found in domestic treated wastewater are valuable and can be reutilized in urban agriculture as a potential strategy to provide communities with access to fresh produce. In this paper, this proposition is examined by conducting a field study in the rapidly developing city of Hyderabad, India. Urban agriculture trade-offs in water use, energy use and GHG emissions, nutrient uptake, and crop pathogen quality are evaluated, and irrigation waters of varying qualities (treated wastewater, versus untreated water and groundwater) are compared. The results are counter-intuitive, and illustrate potential synergies and key constraints relating to the food–energy–water–health (FEW–health) nexus in developing cities. First, when the impact of GHG emissions from untreated wastewater diluted in surface streams is compared with the life cycle assessment of wastewater treatment with reuse in agriculture, the treatment-plus-reuse case yields a 33% reduction in life cycle system-wide GHG emissions. Second, despite water cycling benefits in urban agriculture, only <1% of the nutrients are able to be captured in urban agriculture, limited by the small proportion of effluent divertible to urban agriculture due to land constraints. Thus, water treatment plus reuse in urban farms can enhance GHG mitigation and also directly save groundwater; however, very large amounts of land are needed to extract nutrients from dilute effluents. Third, although energy use for wastewater treatment results in pathogen indicator organism concentrations in irrigation water to be reduced by 99.9% (three orders of magnitude) compared to the untreated case, crop pathogen content was reduced by much less, largely due to environmental contamination and farmer behavior and harvesting practices. The study uncovers key physical, environmental, and behavioral factors that constrain benefits achievable at the FEW-health nexus in urban areas.